Synergy of Indonesia Armed Forces and Riau Islands Regional Government in Preventing the Transmission of the COVID-19 Pandemic - Kurniadi, Anwar (Technium Social Sciences Journal, 2022)
For the Indonesia Armed Forces (IAF), the Riau Islands Province which is dominated by 70% by the ocean is a challenge that must be overcome in successfully preventing the transmission of the COVID-19 pandemic.The purpose of this study was to determine the synergy between IAF and the Riau Archipelago Regional Government in overcoming the transmission of the COVID-19 pandemic. This research used qualitative method with descriptive design. The results showed that: a. the implementation of the Provincial Level COVID-19 Pandemic Task Force as commander of the task force; b. socializing WWK (wearing a mask, washing hands, and keeping a distance) and 3 T (Testing, Tracing, Treatment) in the community, both cities and villages; c. prevention of transmission in border areas, especially IMW entry and exit from abroad such as in Batam and the Natuna Islands; d. support the operation of a special infection hospital (RSKI) on Galang Island which is used as a reference for handling the COVID-19 pandemic; e. distribution of logistics in the form of medical equipment and health materials to all remote areas involving the Army, Navy, and Air Forces; and f. carrying out vaccination activities from cities to border areas. The practical implication is that the synergy between the IAF and the Regional Government of the Riau Islands Province is an example for other regions in Indonesia even though the natural conditions are dominated by water.